(x+half)(x-17)=0

Simple and best practice solution for (x+half)(x-17)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+half)(x-17)=0 equation:


Simplifying
(x + half)(x + -17) = 0

Reorder the terms:
(afhl + x)(x + -17) = 0

Reorder the terms:
(afhl + x)(-17 + x) = 0

Multiply (afhl + x) * (-17 + x)
(afhl(-17 + x) + x(-17 + x)) = 0
((-17 * afhl + x * afhl) + x(-17 + x)) = 0
((-17afhl + afhlx) + x(-17 + x)) = 0
(-17afhl + afhlx + (-17 * x + x * x)) = 0
(-17afhl + afhlx + (-17x + x2)) = 0
(-17afhl + afhlx + -17x + x2) = 0

Solving
-17afhl + afhlx + -17x + x2 = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '17x' to each side of the equation.
-17afhl + afhlx + -17x + 17x + x2 = 0 + 17x

Combine like terms: -17x + 17x = 0
-17afhl + afhlx + 0 + x2 = 0 + 17x
-17afhl + afhlx + x2 = 0 + 17x
Remove the zero:
-17afhl + afhlx + x2 = 17x

Add '-1x2' to each side of the equation.
-17afhl + afhlx + x2 + -1x2 = 17x + -1x2

Combine like terms: x2 + -1x2 = 0
-17afhl + afhlx + 0 = 17x + -1x2
-17afhl + afhlx = 17x + -1x2

Reorder the terms:
-17afhl + afhlx + -17x + x2 = 17x + -17x + -1x2 + x2

Combine like terms: 17x + -17x = 0
-17afhl + afhlx + -17x + x2 = 0 + -1x2 + x2
-17afhl + afhlx + -17x + x2 = -1x2 + x2

Combine like terms: -1x2 + x2 = 0
-17afhl + afhlx + -17x + x2 = 0

The solution to this equation could not be determined.

See similar equations:

| 2-5x=2x | | 25sin(wt)+20cos(wt)=17 | | X^2-3x=260 | | 7x+13=2x-12 | | -2(4+x)=10-(x-2) | | 4a+7b=180 | | 2x+11=51+2x | | -4x+9=-6+11x | | x^2-2xy-y^2+3x-8y+5=0 | | 2.4/4=n/6 | | x^2-2xy-y^2+3x-8y+5=o | | f(x)=2+y | | x-6=-7+(x-5) | | j^3-8=0 | | 121p^2+25q^2=0 | | X(x-16)=-32(x+2) | | 2m-6=42 | | 2x/5-180=2 | | 3y-12=2x-5 | | -6j^3-48=0 | | s^2t+s^2u^2+tv+u^2v=0 | | 0.4x+0.7y=0.6(30) | | 1/2(-16s-20)=-8s-10 | | X/2=1/6 | | -4y=2+y | | 1/5/6=x/60 | | 6x-(x+3)=2x+5 | | j^4-16=0 | | x^2=283 | | (y-1)=t | | -2-7k=-k+20 | | 4x^2+16x+7=0 |

Equations solver categories